1985
DOI: 10.7601/mez.36.197
|View full text |Cite
|
Sign up to set email alerts
|

Removal sampling of male mosquitoes from field populations by sound-trapping

Abstract: Sound trappin.cr of male mosquitoes in the field svas impros'ed ",ith the introduction of an artificial swarm marker. A 1 × 2.5 m black cloth was wrapped around the base of a O.7-m high tripod, and two or four sound traps were hunsr above the cloth at O.7 and 1.5m, During dusk, 370Hz sound at 100dB was emitted for 5-sec duration and at 15-sec intervals by each speaker to trap Culex tarsalis and Culex tritaeniorh},nchus. The sound-trapped mosquitoes were mostly 3and 4-day-old males. The standard deviation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…As females lack plumose antennae, it has been suggested that only males are capable of discriminating the species of the incoming females (Clements, 1963;and references therein). Based on this model, Roth (1948) and Ikeshoji et al (1985) were successful in trapping male Aedes aegypti using synthezised sound played in the field at a frequency characteristic of females. Brogdon (1998) discovered that different flight tones characterize laboratory colonies of sympatric members of the An.…”
Section: Discussionmentioning
confidence: 99%
“…As females lack plumose antennae, it has been suggested that only males are capable of discriminating the species of the incoming females (Clements, 1963;and references therein). Based on this model, Roth (1948) and Ikeshoji et al (1985) were successful in trapping male Aedes aegypti using synthezised sound played in the field at a frequency characteristic of females. Brogdon (1998) discovered that different flight tones characterize laboratory colonies of sympatric members of the An.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a short range of acoustic detection may be a general rule for insects like the Mediterranean fruit ßy that detect sound with particle velocity sensors by using antennal ßagellar or JohnstonÕs organs (Tautz 1979). A Ͻ1-m active space has been reported in mosquitoes (Ikeshoji et al 1985, Ikeshoji andOgawa 1988), midges (Ogawa 1992, Hirabayashi andOgawa 1999), ants (Hickling and Brown 2000), honey bees (Towne and Kirchner 1989), and caterpillars (Tautz and Markl 1978).…”
Section: Resultsmentioning
confidence: 98%
“…Several mosquito (Ikeshoji et al 1985, Ikeshoji andOgawa 1988) and midge (Ogawa 1992, Hirabayashi andOgawa 1999) species have been captured in shortrange acoustic traps. Males initially attracted to a swarm marker were captured in adhesive or other traps next to speakers broadcasting recorded wingbeats or synthetic mimics of sounds produced by ßying conspeciÞc females.…”
mentioning
confidence: 99%
“…Insects of different species attracted to sound have been trapped by a variety of devices, including electrically charged screens [10,11,69], fans or vacuums [64] with collecting bags or cones with nets [66], adhesive cylinders [12,[70][71][72] and boards [14], funnel and bucket traps [73], or wood-and-screen silt traps [74]. The preferred traptype depends partly on the size of the insect and its locomotory behaviours, i.e., flight or walking up or down a surface, preferences for crevices or holes, rough or smooth surfaces, etc.…”
Section: Attraction and Trapping Devicesmentioning
confidence: 99%
“…Traps using sound to attract insects were first reported in 1949 in studies where male Anopheles albimanus Wiedemann mosquitoes were captured in experiments with loudspeakers [10,11]. Subsequently, acoustic methods were developed in field and laboratory studies to trap other mosquitoes [12][13][14][15][16], Chironomid midges [17][18][19][20], Scapteriscus spp. mole crickets [7,21], gryllid field crickets and their tachinid parasitoids [22,23], Achroia and Galleria moths [24,25], Blattella germanica (L.) cockroaches [26] and tephritid fruit flies [27][28][29].…”
Section: Introductionmentioning
confidence: 99%